The dawn of digital TV. - Rast, R.M (IEEE spectrum)
The end of analog TV is at hand. Governments are setting firm dates and planning for the new broadcast TV. Although analog TV is being shutdown, it is observed that changing to digital TV costs much higher mainly because of its convenience in connectivity, crisp quality images and digital sounds. In the end, though, consumers are winners, with new and improved services available. They have access to HDTV's great pictures and sound. Thy have uniformly high-quality reception anywhere in a broadcast area, and additional services includes some within traditional broadcast channels but even more coming in the auctioned broadcast spectrum.